New localities and habitat preferences of common milkweed Asclepias syriaca L. in Toruń (Central Poland) - Rutkowski, Lucjan; Kamiński, Dariusz; Nienartowicz, Andrzej; Filbrandt-Czaja, Anna; Adamska, Edyta; Deptuła, Miłosz (Ecological Questions, 2016)
The paper presents the location and general description of habitats and plant communities with common milkweed occurring within the city limits of Toruń. The data set comprised new localities of this species as well as those where Asclepias syriaca has been observed for several years but the sites have not been described in the ecological literature. Relevés made at these sites were compared with those described by Puchałka et al. (2013) from three sites of Asclepias syriaca in Toruń. A larger set of new sites included in the analysis allows for a more accurate description of the impact exerted by some ecological factors, e.g. afforestation, on the growth of the studied species. As evidenced by the new sites of Asclepias syriaca found recently in Toruń and the surrounding area, it is necessary to monitor the dynamics of the population and to undertake the research on the impact of common milkweed on plant communities.